RECORDS OF SIX SPECIES OF CARANGIDS FROM THE SOUTHWEST COAST OF INDIA - Sreenivasan, P V (Indian Journal of Fisheries, 2011)
Fishes of the family Carangidae are widely distributed along both the coasts of India and form about 2% of the total marine fish landings of this country. At Vizhinjam area, along the south west coast of India, there exists a prosperous fishery for carangids which form 15-16% of the total annual catch.